Taboo Language, Masculinity, and Social Transgression in Gillian Flynn’s Gone Girl (PANOPTICON: Journal of English Studies, 2026)
This study examines how Nick Dunne, portrayed as a socially transgressive figure, employs taboo language and engages in taboo behavior toward Amy and within his broader public environment in Gillian Flynn’s Gone Girl (2014). Although numerous studies have explored characterization and gender in the novel, limited attention has been given to the sociolinguistic dimensions of taboo language and behavior as reflections of masculine anxiety. This research adopts a qualitative descriptive method. Data were collected through close reading and systematic analysis of Nick’s utterances and actions throughout the novel. The theoretical framework integrates Battistella’s (2005) classification of taboo words (epithets, profanity, vulgarity, and obscenity), Jay’s (2009) categorization of profanity and obscenity, Wardhaugh et al.’s (2014) functions of taboo language, Fershtman et al.’s (2011) perspective on taboo behavior in social interaction, and Connell’s (2014) theory of masculinity and gender-based taboos. The findings reveal two principal results. First, obscenity emerges as the most dominant type of taboo language, primarily functioning to express emotional intensity. Second, there is a significant connection between Nick’s violation of male gender taboos and broader social taboos. His failure to fulfill the traditional role of breadwinner and his passivity within the marriage represent violations of hegemonic masculinity, which subsequently motivate his engagement in social taboo behaviors, including deception and manipulation. These actions are portrayed as attempts to avoid public stigma and the identity of a “failed man,” rather than as responses centered on Amy’s disappearance.